Analisis Deteksi Kedalaman Retak Pada Beton Mengunakan Metode UPV Testing: Studi Penelitian - Rifdah Mufiidah Harahap; Darlina Tanjung; M Husni Malik Hasibuan; Marwan Lubis (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
Non-destructive tests are currently widely used in evaluating the quality of concrete installed in the field. One NDT is using the Ultrasonic Pulse Velocity (UPV) method. In general, the use of UPV in concrete is to estimate concrete strength, determine the homogeneity of concrete and detect concrete damage, for example the presence of voids or cracks. This research is intended to determine the accuracy of UPV test results in detecting concrete cracks at several variations in crack depth. In this research, the UPV tool validation process was carried out by making 1 type of test object. Namely 1 beam specimen for testing crack depth (UPV) with 6 variations of artificial cracks where the artificial cracks are made using plywood. Each sample has been treated so that it can describe the crack depth according to the existing plan. In testing, it was found that the estimated crack depth in variation I was 33.2 mm deep, variation II was 18.8 mm deep, variation III was 104.4 mm deep, variation IV was 115.8 mm deep, variation V was 24.4 mm deep and variation VI 159.3 mm deep. And the average accuracy is 13.60%. The smaller the wave travel time, the smaller the crack depth, the smaller the wave emission and the longer the wave path to detect cracks. which means that the accuracy of UPV crack depth testing tends to decrease with the unevenness of the concrete surface.